Respuesta :
Step-by-step explanation:
z = 5y/8
x = 3y/8
2x + 3y - z = 50
6y/8 + 3y - 5y/8 = 50
6y/8 + 24y/8 - 5y/8 = 50
25y/8 = 50
25y = 400
y = 16
x = 3y/8 = 3×16/8 = 3×2 = 6
z = 5y/8 = 5×16/8 = 5×2 = 10
x/3=y/8=z/5
2x+3y-z=50
x/3=y/8
x/3=z/5
2x+3y-z=50
8x-3y=0
5x-3z=0
2x+3y-z=50
x=3/8y
5x-3z=0
2x+3y-z=50
5×3/8y-3z=0
2×3/8y+3y-z=50
15y-24z=0
-15y+4z=-200
-20z=-200
z=10
15y-24×10=0
y=16
x=3/8×16
x=6
(x, y, z)=(6, 16, 10)
Hope my answer helped u :)
2x+3y-z=50
x/3=y/8
x/3=z/5
2x+3y-z=50
8x-3y=0
5x-3z=0
2x+3y-z=50
x=3/8y
5x-3z=0
2x+3y-z=50
5×3/8y-3z=0
2×3/8y+3y-z=50
15y-24z=0
-15y+4z=-200
-20z=-200
z=10
15y-24×10=0
y=16
x=3/8×16
x=6
(x, y, z)=(6, 16, 10)
Hope my answer helped u :)